2001
DOI: 10.1139/y01-047
|View full text |Cite
|
Sign up to set email alerts
|

Sarpogrelate diminishes changes in energy stores and ultrastructure of the ischemic-reperfused rat heart

Abstract: Although the involvement of serotonin in exacerbating vascular abnormalities in ischemic heart disease has been established, its role in mediating changes in cardiac function due to ischemia reperfusion (IR) is poorly understood. The aim of this study was to investigate the effect of a serotonin blocker, sarpogrelate (5-HT2A antagonist), in preventing cardiac injury due to IR. Isolated rat hearts were subjected to 30 min of global ischemia followed by 1 h of reperfusion. Sarpogrelate (50 nM-0.9 microM) was inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Depletion of 5-HT by paracholorophenylalanine exerted a cardioprotective effect similar to that observed with 5-HT 2 antagonists, suggesting that antagonists of 5-HT 2 receptors play an important role in cardioprotection in ischemia-reperfusion (40). Moreover, treatment of isolated rat heart with sarpogrelate for 10 min before ischemia and 60 min during reperfusion also caused improvement in cardiac function (148). Ischemia-reperfusioninduced changes in left ventricular developed pressure, left ventricular diastolic pressure, maximum rate of pressure development and maximum rate of pressure decay were restored by different concentrations of sarpogrelate (Fig.…”
Section: Effects In Heart Failure and Myocardial Infarctionsupporting
confidence: 55%
See 1 more Smart Citation
“…Depletion of 5-HT by paracholorophenylalanine exerted a cardioprotective effect similar to that observed with 5-HT 2 antagonists, suggesting that antagonists of 5-HT 2 receptors play an important role in cardioprotection in ischemia-reperfusion (40). Moreover, treatment of isolated rat heart with sarpogrelate for 10 min before ischemia and 60 min during reperfusion also caused improvement in cardiac function (148). Ischemia-reperfusioninduced changes in left ventricular developed pressure, left ventricular diastolic pressure, maximum rate of pressure development and maximum rate of pressure decay were restored by different concentrations of sarpogrelate (Fig.…”
Section: Effects In Heart Failure and Myocardial Infarctionsupporting
confidence: 55%
“…It has only insignificant 5-HT 1 , 5-HT 3 , 5-HT 4 , á 1 -adrenoceptor, á 2 -adrenoceptor, â-adrenoceptor, H 1 and H 2 histaminic receptor, and M 3 muscarinic receptor antagonistic activities (80,97,107). Sarpogrelate has been found to have protective effects in the treatment of peripheral vascular occlusive diseases (52), thromboangitis obliterans (93), effort angina (146), congestive heart failure (13,14), atherosclerosis (45,132), restenosis after coronary stenting (32), pulmonary hypertension (88), and ischemia/reperfusion induced myocardial injury (148). It seems likely that sarpogrelate has therapeutic potential by attenuating 5-HT 2A receptor activation-mediated cardiac abnormalities in various diseases.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in agreement with previous results indicating that stimulation of 5-HT receptors is involved in postreperfusion cardiac damage rather than cardioprotection. 6,31,32 Interestingly, MAO inhibitors also decreased cardiac damage after I/R when administered 10 minutes before reperfusion. These results suggest that MAO inhibitors may have clinical relevance for the prevention of postreperfusion cardiac injury by treating patients in the period occurring between the ischemic event and reperfusion.…”
Section: Discussionmentioning
confidence: 96%
“…Nonaka et al (14) showed that platelets strongly affected hyperacute xenorejection in an ex vivo guinea pig model of perfused lung grafts and that SH administration reduced lung edema. Other investigations also reported that SH had cardioprotective effect on ischemia/reperfusion injury in isolated rat or guinea-pig hearts (15,16). Hayashi et al demonstrated another beneficial effect of SH.…”
mentioning
confidence: 95%